Social media and visit decision to tourist destinations: measuring the impact of instagram on expatriates in Indonesia - Prisgunanto, Ilham (Penerbit Universiti Kebangsaan Malaysia, 2020)
The Indonesian government has huge interests in increasing the number of tourists visiting Indonesia. Social media have been argued to have significant roles in influencing people to visit tourist destinations. Based on the uses and gratification perspective, this study aims to examine whether social media, especially Instagram, influence people, especially expatriates, in deciding to visit tourist destinations in Indonesia. The respondents were 100 foreigners or expatriate workers who live in Indonesia, particularly in Tangerang Selatan regency. The questionnaires were distributed among the sample from August to November 2018. The hypothesis was tested using a simple linear regression method. For the analysis, this study has applied a semantic differential scale. This study concludes that the influence of Instagram to the foreign workers' decision to visit tourist destinations in Indonesia is indeed very small, only 11.2%. Instagram, for most netizens, is used not only to seek information regarding tourism services and facilities but more importantly to build relationships among netizens. The shared information will not be fully trusted by netizens, but would rather be assessed and evaluated by first looking at the reputation of the person who provides the information. This study also finds that information sharing on Instagram is not correlated necessarily to the netizens' attitudes and behaviors, particularly towards their desires to visit Indonesian destinations. However, social media are used as a reference for the future visit.